2022
DOI: 10.53730/ijhs.v6ns2.8767
|View full text |Cite
|
Sign up to set email alerts
|

Impact of online education on medical students

Abstract: Introduction: - COVID-19 is the most significant viral disease spread by a coronavirus, is developing very fast all over the world, and it is becoming a world threat. Crisis e.g. pandemic situation harms the education process, and academic function. To destroy the barriers that covid-19 creates, the government decided to start classes on an online platform. Then in 2020, all universities and colleges will provide education through an online platform. This study aims to detect how medical students get classes, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 10 publications
0
3
0
Order By: Relevance
“…62.7% students marked other issues including demonstration issues, patient history taking difficulties, and hand on exposure issues. 15 In our study most of the students (52.74%) did not recommend such type of online classes for upcoming medical students in future and only 16.25% students recommend this online platform. Another similar study in India, 58.3% medical students did not recommend this online class for medical students in future and only 13.8% students recommend this.…”
Section: Discussionmentioning
confidence: 56%
See 2 more Smart Citations
“…62.7% students marked other issues including demonstration issues, patient history taking difficulties, and hand on exposure issues. 15 In our study most of the students (52.74%) did not recommend such type of online classes for upcoming medical students in future and only 16.25% students recommend this online platform. Another similar study in India, 58.3% medical students did not recommend this online class for medical students in future and only 13.8% students recommend this.…”
Section: Discussionmentioning
confidence: 56%
“…Also eyesight problems, depression, anxiety were developed in 17.2%, 12.9% and 9.3% medical student's respectively. 15 Our study revealed that 91.13% students used mobile phone for attending online classes. Laptop, tablet including ipad, desktop were used by 27.42%, 20.67%, 3.79% medical students respectively.…”
Section: Discussionmentioning
confidence: 71%
See 1 more Smart Citation